The Tradition of Maantaan Sala in Nagari Guguak Malalo: An Analysis of ‘Urf as a Method of Derivation in Islamic Law - Ulfa, Rusda; Azwar, Zainal (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2025)
The Maantaan Sala tradition in Nagari Guguak Malalo, West Sumatra, represents a customary engagement ceremony in which the bride’s family presents special dishes to the groom’s family. This study seeks to examine the Maantaan Sala tradition through the lens of ‘urf (custom) as a source of Islamic law, with the aim of assessing its conformity with the principles of sharia and the values of public benefit (mashlahah). This research adopts a qualitative field approach, utilising primary data collected through semi-structured interviews with traditional leaders (Ninik Mamak) and the Head of the Customary Council (KAN). Secondary data includes customary documents (Adaik Salingka Nagari Guguak Malalo), books, and academic journals. The data were analysed descriptively through three stages: interview transcription, data coding, and interpretation based on ‘urf theory in Islamic law. The findings indicate that Maantaan Sala functions as a formal public declaration of engagement that embodies social and religious values, including the upholding of honour, the strengthening of kinship ties, the demonstration of filial respect, and the prevention of “a proposal over another proposal,” which is prohibited in Islam. Philosophically, the offering of traditional dishes such as talam samba, which contains rendang, bubua kuniang (yellow sticky rice), and sirih pinang (betel quid), symbolizes honour, prudence, and respect for parental values—principles that align with Islamic moral teachings. According to ‘urf theory, this tradition qualifies as ‘urf shahih (valid custom) due to its widespread acceptance, continuous practice, social benefits, and lack of contradiction with sharia texts. Academically, this study contributes to the enrichment of socio-cultural fiqh scholarship and opens avenues for further research on the living values of Islamic law within local customary traditions.